Penerapan Metode Selft Organizing Maps (SOM) Dalam Rekomendasi Jurusan Calon Mahasiswa Baru (Studi Kasus : Universitas Imelda Medan) - Harika Fitri Sinurat; Surya Darma Nasution; Alwin Fau (STMIK Budi Darma, 2020)
Admission of new students is an administrative process for prospective students in educational institutions. This process is usually carried out every year. Imelda University Medan is one of the universities that still uses manual system procedures in selecting the right majors for prospective new students. This study aims to design a data mining system application for recommendations for new student majors at Imelda University Medan, using the Selft Organizing Maps (SOM) method to make it easier for prospective new students in the process of selecting the right department. For application design, the Visual Basic 2008 programming language is used, this system is made flexible so that if at any time the criteria used can be adjusted according to needs. The results of this study indicate that the SOM method can produce recommendations for the right majors for prospective students at the University of Imelda Medan. . Thus the system is expected to be able to assist in the activities of department recommendations for prospective new students at the University of Imelda Medan.Keywords: New Students, Data mining, Selft Organizing Maps (SOM)